Gestational Surrogacy: Current View. (February 2019) - Aznar, Justo; Martínez Peris, Miriam
Surrogate motherhood is an assisted procreation practice by which a woman gestates an embryo with which she has no biological relationship on behalf of a contracting couple or individual, having to relinquish the child to them after its birth. This practice normally entails a financial remuneration for the pregnant woman; when this is not the case, it is called altruistic surrogacy. From a medical perspective, potential problems for the surrogate and for children born through this practice should be taken into account, especially the existence of possible disabilities in the child. The bioethical aspects are of most interest because the practice of surrogacy objectifies the expectant mother, by using her body for a purpose other than her own good, treating her as a commodity, as a thing. The same is true for the child because it makes him a disposable object, something that can be instrumentalized, similarly objectifying him.